2017
DOI: 10.18388/abp.2016_1495
|View full text |Cite
|
Sign up to set email alerts
|

Effects and time-kill assessment of amoxicillin used in combination with chloramphenicol against bacteria of clinical importance

Abstract: With the emergence of multidrug-resistant organisms in an era when drug development faces challenges causing pharmaceutical companies to curtail or abandon research on anti-infective agents, the use of combined existing antimicrobial agents may be an alternative. This study evaluated the effects of combining amoxicillin and chloramphenicol, to which many bacteria have become resistant, in vitro against Gram positive and Gram negative bacteria by agar diffusion, checkerboard and time-kill assays. The test isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The unreasonable use of these antibiotics leads to an increase in bacterial drug resistance. Preparing an AMO compound formulation is a good strategy for decreasing the bacterial drug resistance of AMO[ 34 ]. BCL, an active ingredient extracted from S. baicalensis , has been used in the Chinese market for years, and the API form of BCL (content > 85%) is RSE.…”
Section: Discussionmentioning
confidence: 99%
“…The unreasonable use of these antibiotics leads to an increase in bacterial drug resistance. Preparing an AMO compound formulation is a good strategy for decreasing the bacterial drug resistance of AMO[ 34 ]. BCL, an active ingredient extracted from S. baicalensis , has been used in the Chinese market for years, and the API form of BCL (content > 85%) is RSE.…”
Section: Discussionmentioning
confidence: 99%
“…This study is in agreement with Alou et al [40] and Jacqueline et al [41] who reported that many in vitro antibiotic combinations have resulted in no interaction and/or synergistic interactions. While the synergy potentially increases efficacy, reduces toxicity, cures faster, prevents the emergence of resistance and provides broader-spectrum of activity than monotherapy regimens [42], the synergistic interactions between ciprofloxacin and metronidazole could have the potential to not only increase the rate of initial treatment response [43,44] but could also reduce the concentration of each antibiotic needed to elicit a given effect and consequently improve the therapeutic index [45].…”
Section: Discussionmentioning
confidence: 99%